Characterisation of a perpendicular nanomagnetic cell and design of reversible XOR gates based on perpendicular nanomagnetic cells. Issue 1 (20th December 2019) - Sayedsalehi, Samira; Azadi Motlagh, Zeinab
Abstract : The purpose of this research is to find out a perpendicular nanomagnetic cell with optimum dimensions by using Object Oriented Micromagnetic Framework (OOMMF) simulation. The optimum perpendicular nanomagnetic cell is characterised and the effect of nano‐size on the performance of the cell is explored. Nanomagnetic basic gates are implemented by applying the proper arrangement of nanomagnetic cells. The optimum size of nano cell is 50 × 30 × 5 nm. In this survey, all designs are implemented by employing 3‐input and 5‐input minority gates. The clock signal, which is a uniform magnetic external field, is needed for proper performance of gates. An irreversible 2‐input XOR gate is suggested by these gates based on perpendicular nanomagnetic cells. Moreover, the power dissipation is a major concern in digital circuits. It was proved that the heat dissipation will be very low in reversible circuits. Therefore, the reversible XOR gates are suggested by applying the proposed gates in this study. The correctness of operation of the presented gates is verified by using MagCAD tool. According to the simulation results, the proposed 2‐input XOR gates in a single layer have significant improvement in terms of gate count, delay and complexity in comparison to the previous design.